Load and fatigue monitoring in musicians using an online app: A pilot study - McCrary, J. Matt; Ascenso, Sara; Savvidou, Paola; Schraft, Séverine; McAllister, Lesley; Redding, Emma; Bastepe-Gray, Serap; Altenmüller, Eckart (Frontiers in Psychology, 2022)
Background/Aims: High occupational injury rates are reported in musicians, with a career prevalence of up to 89%. Fatigue and playing (over)load are identified as key risk factors for musicians’ injuries. Self-report fatigue management strategies in sport have demonstrated preventive effects. A self-report fatigue management tool for musicians was developed based on a Delphi survey of international experts and hosted in an online app. The aims of this study are to evaluate the content validity and uptake of this new tool, and explore associations between collected performance quality, physical/psychological stress, pain, injury and fatigue data. Methods: University and professional musicians were asked to provide entries into the online app twice per week for one to six months. Entries into the app were designed to take 2-3 minutes to complete and consisted of the following: 6 questions regarding playing load over the previous 72 hours; 5 questions regarding current levels in key physical/ psychological stress domains (sleep, recovery, overplaying, pain, fitness); one question self-rating of performance quality over the previous day; one question regarding current musculoskeletal symptoms; a reaction time task to evaluate psychomotor fatigue. Results: N=96 participants provided an average of 2 app entries (range 0 – 43). Increased playing time, rating of perceived exertion (RPE), and feelings of having to ‘play too much’ were consistently associated with increased self-rated performance quality (p<.004; 6.7